Statistical analysis of wind energy potential of Elazig province according to Weibull and Rayleigh distributions - Akpinar, Ebru Kavak; Balpetek, Nilay (Gazi Univ, Fac Engineering Architecture, 2019)
In this study, the statistical analysis of wind power density and wind speed distribution parameters in Elazig province was investigated using the hourly wind speed data measured by the General Directorate of Meteorology between 2005 and 2014. Weibull and Rayleigh distributions were used for modeling and the success of this modeling process was evaluated according to the parameters of R-2, RMSE and chi(2). According to statistical criteria in wind data analysis of Elazig province. Weibull distribution is better than Rayleigh distribution.
Weibull ve Rayleigh dağılımlarına göre Elazığ ilinin rüzgâr enerjisi potansiyelinin istatiksel analizi
Keywords: Wind energy; statistically analysis of the wind energy potential; Weibull distribution; Rayleigh distribution; Elazig